The picture is not clear. let me assume
y = (x^4)ln(x^3)
product rule :
d f(x)g(x) = f(x) dg(x) + g(x) df(x)
dy/dx = (x^4)d[ln(x^3)/dx] + d[(x^4)/dx] ln(x^3)
= (x^4)d[ln(x^3)/dx] + 4(x^3) ln(x^3)
look at d[ln(x^3)/dx]
d[ln(x^3)/dx]
= d[ln(x^3)/dx][d(x^3)/d(x^3)]
= d[ln(x^3)/d(x^3)][d(x^3)/dx]
= [1/(x^3)][3x^2] = 3/x
... chain rule (in detail)
end up with
dy/dx = (x^4)[3/x] + 4(x^3) ln(x^3)
= x^3[3 + 4ln(x^3)]
Answer:
5 9/20
Step-by-step explanation:
4 7/10 + 6/8
Simplify the fractions by dividing the second top and bottom by 2
4 7/10 + 3/4
Getting a common denominator of 20
4 7/10 *2/2 + 3/4 * 5/5
4 14/20 + 15/20
4 29/20
4 + 20/20 + 9/20
4+1+9/20
5 9/20
Answer:
8
Step-by-step explanation:
sammy has 8 and ellen has 24 then add sammy's 8
24+8=32
Answer:
Radius
Step-by-step explanation:
I know the answer